Observational Study of Atlas Vertebra in South Karnataka Population with Special Reference to Retro Articular Canals and Foramina Transversarium (Indian Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Atlas Vertebra (1st cervical vertebra) is called “atypical vertebra” and has unusual shape andarchitecture. The dimensions of atlas vertebra are most essential in the technique of cranio-vertebral regionstabilization. The Retroarticular canals and foramina transversaria are important for transoral transpalatinalapproaches to clivus, atlas and axis.Aim and objectives: To study the incidence of Retroarticular canals and symmetry of foramina transversaria.Materials and Methods: The material for the present study consists of 100 adult intact human atlases of unknownsexes. They were collected from the department of anatomy, MS Ramaiah Medical College.Results: Total number of incidences of retroarticular canals were 10 , 6 were present on right and 4 were on left, Outof 6 on right side 3 were complete and 3 were incomplete ,on left side 2 were complete and 2 were incomplete. Theforamina transversaria are more prominent on right side in 29 vertebrae as compared to left prominence, whichwas observed only in 15 atlas vertebrae. But in majority of cases (60 atlas vertebrae) the foramina transversariaare equal in size.Conclusion: The study was conducted in 100 atlas vertebrae The observations on retroarticular canals andsymmetry of foramina transversaria did show significant results. This study will be useful for the forensicanatomists, forensic anthropologists, radiologists, neurosurgeons and orthopedic surgeons
Keywords: Atlas vertebra, Retroarticular canals, symmetry of foramina transversaria.